Maternal inheritance of grain iron and zinc densities in pearl millet - Kanatti, Anand; Govindaraj, Mahalingam; Rai, Kedar Nath; Rao, Aluri S. (Indian Society of Genetics & Plant Breeding, 2019)
Genetic variation and inheritance of micronutrients in pearl millet has largely been studied in recent years as part of biofortification initiatives. In this study, maternal (reciprocal) effect on inheritance of grain Fe and Zn was studied using a set of diverse breeding material. Entries were paired for low and high for Fe density to produce direct and reciprocal crosses. Over two-seasons, Fe density among parents varied 31-64 mg kg–1 and Zn density varied 28-43 mg kg–1. Difference between each direct and reciprocal crosses for Fe (1 to 4 mg kg–1) and Zn (0 to 2 mg kg–1) were negligible and non-significant, hence cytoplasmic or maternal genes are not likely to modify inheritance of these traits. These results indicate that high Fe/Zn inbred can be used either as female or male parent in hybrid-parent breeding program.